EFL University Students’ Translation Beliefs in Reading Comprehension and Its Correlation with Their Reading Comprehension - Setianing Rizki, Deka Dwi (RETAIN, 2021)
Translation is believed toelp students to obtain good comprehension in reading because according to the process of translation, it helps students to comprehend the content of a text. Yet the use of translation was prohibited since in the end of 19th century. However, it is still useful if it is used properly. Therefore, this present study was conducted to explore translation beliefs in reading comprehension of EFL university students and its correlation with their reading comprehension. To conduct the participants’ translation beliefs, it implemented descriptive quantitative analysis. The data were acquired online towards 80 English department students. The questionnaire covers 5 Likert-scale questionnaire of students’ translation beliefs in reading comprehension, and the students’ TEP (Test of English Proficiency) score for reading comprehension score was also required. The result of the descriptive quantitative analysis revealed that most of the students thought that translation bring positive impact such as understanding new vocabulary or phrase, and grasp idea in each paragraph of an English text (M=3.68). Also, most of the students felt translation was useful and enjoyable (M=3.58). For the correlation, the result of Pearson Product Moment showed that the correlation between students’ translation beliefs in reading comprehension and their reading comprehension was negatively correlated (p value = .001) with low coefficient level (r = - .370). Thus, the correlation between the variables was opposite. The more the participants had translation beliefs, the lower reading comprehension score they had and vice versa.